Le duc de Bourgogne et son reliquaire de Liège (1467-1471) - Philippe George (Bulletin du Centre d’Études Médiévales d’Auxerre)
The reliquary known as Charles the Bold’s reliquiary (gold, silver and enamel, h. 53 cm, overall weight c. 5 kg), a major work of Belgian national heritage, was produced between 1467 and 1471 by the goldsmith Gérard Loyet. Since the last major publications (2000-2012), new elements have still appeared in the dossier. We formulate here some unpublished hypotheses in the reading of this goldsmith group which has been restored and has just been definitively put in place at the Liège Cathedral Treasury.